2017
DOI: 10.1111/bjc.12168
|View full text |Cite
|
Sign up to set email alerts
|

Individual and interpersonal emotion regulation among adults with substance use disorders and matched controls

Abstract: Compared to matched controls, adults with substance use disorders self-report significantly more difficulties with emotional awareness and regulation. Compared to matched controls, adults with substance use disorders report significantly greater expectancies not to show depression and anxiety. When viewing positive and negative images, adults with substance use disorders are significantly less flexible in their facial expression of emotion than matched controls in response to regulatory instructions. Emotion r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(42 citation statements)
references
References 59 publications
3
33
0
6
Order By: Relevance
“…In addition to mood and anxiety disorders, other research indicates that difficulties in interpersonal emotion regulation also affects the risk and maintenance of substance use and personality disorders, such as borderline personality disorder, as well as post-traumatic stress disorder (PTSD) symptomology. For example, Dingle, Neves, Alhadad, and Hides (2018) examined interpersonal emotion regulation in adults with or without substance use disorders and found differences related to the regulation, sharing, and awareness of emotions. Specifically, those with substance use problems expected that they would not experience anxious or depressed feelings, as measured by the Social Emotion Expectancy Scale.…”
Section: Interpersonal Emotion-regulation Outcomesmentioning
confidence: 99%
“…In addition to mood and anxiety disorders, other research indicates that difficulties in interpersonal emotion regulation also affects the risk and maintenance of substance use and personality disorders, such as borderline personality disorder, as well as post-traumatic stress disorder (PTSD) symptomology. For example, Dingle, Neves, Alhadad, and Hides (2018) examined interpersonal emotion regulation in adults with or without substance use disorders and found differences related to the regulation, sharing, and awareness of emotions. Specifically, those with substance use problems expected that they would not experience anxious or depressed feelings, as measured by the Social Emotion Expectancy Scale.…”
Section: Interpersonal Emotion-regulation Outcomesmentioning
confidence: 99%
“…For example, others can help a depressed person to distract from a negative situation, to shift attention to more neutral and positive stimuli, and can support cognitive change through the explicit correction of unhelpful cognitions or by emphasizing schema‐inconsistent information to the depressed person (Marroquín, ). A recent study of adults in residential treatment for substance use disorders found that, in comparison with matched controls, they experience marked difficulties in emotional awareness and regulation, and find it more difficult to regulate their facial expressions of emotion in response to visual stimuli (Dingle, da Costa Neves, Alhadad, & Hides, submitted).…”
Section: Introductionmentioning
confidence: 99%
“…Substance use prevention and treatment efforts then are best able to address the relationships between substance use and mood by considering how emotional experiences underlie or exacerbate maladaptive coping strategies. As noted by Dingle and colleagues [ 39 ], “even following treatment, emotional distress is the number one trigger for relapse into substance misuse” (p. 187). Thus, learning ER skills, particularly the management of distress, holds significant promise in preventing the escalation of AOD misuse to SUDs in young adulthood.…”
Section: An Emotion Regulation Perspective On Young Adults’ Aod Usmentioning
confidence: 99%